2017
DOI: 10.1021/acs.jproteome.6b00845
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid and Maternal Serum Metabolic Signatures in the Second Trimester Associated with Preterm Delivery

Abstract: Preterm delivery (PTD) represents a major health problem that occurs in 1 in 10 births. The hypothesis of the present study was that the metabolic profile of different biological fluids, obtained from pregnant women during the second trimester of gestation, could allow useful correlations with pregnancy outcome. Holistic and targeted metabolomics approaches were applied for the complementary assessment of the metabolic content of prospectively collected amniotic fluid (AF) and paired maternal blood serum sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 49 publications
(73 reference statements)
2
85
1
1
Order By: Relevance
“…As these metabolites exhibit a wide variety of physicochemical properties, a generic extraction procedure is typically applied for LC-MS based metabolomics. Here the simple protein precipitation method often applied in our studies [31], and three alternate methods were compared. Figure 1 depicts schematically the standard PPT and the tree tested procedures.…”
Section: Resultsmentioning
confidence: 99%
“…As these metabolites exhibit a wide variety of physicochemical properties, a generic extraction procedure is typically applied for LC-MS based metabolomics. Here the simple protein precipitation method often applied in our studies [31], and three alternate methods were compared. Figure 1 depicts schematically the standard PPT and the tree tested procedures.…”
Section: Resultsmentioning
confidence: 99%
“…86,87 As mentioned, metabolic profiles can be generated from a variety of biological fluids; this methodologic advantage was recently utilized to demonstrate biomarkers present in amniotic fluid and maternal serum collected during women's second trimester that predicted later preterm delivery. 88 Metabolomics has also been used to identify biomarkers produced in mice uterine tissue following pharmacologic stimulation versus inhibition of contractions, revealing new detail on the mechanisms of uterine contractility in rodents. 89 Our study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials of total LCPUFA supplementation have been conducted and found a reduction in early PTB (<34 weeks) 10,12,13 . The secondtrimester serum lipid profiling of 35 PTB women and 35 matched term delivery controls were carried out, and increased levels of lipids and changes of key end-point metabolites were found in PTB women 14 . All these discoveries imply that lipids could play an important role in PTB and could be used as potential biomarkers for PTB or interventions to extend the length of pregnancy.…”
Section: Background and Summarymentioning
confidence: 99%